2015
DOI: 10.5897/ajb2015.14696
|View full text |Cite
|
Sign up to set email alerts
|

Fenthion induced toxicity and histopathological changes in gill tissue of freshwater African catfish, Clarias gariepinus (Burchell, 1822)

Abstract: Fenthion is an organophosphate pesticide commonly used in agriculture and public health for the control of insect pests. The present study investigated the toxic effect of fenthion and the histopathological alterations in the gill tissue of African catfish Clarias gariepinus. The 96 h LC 50 value of fenthion in C. gariepinus determined by probit analysis was found to be 39.97 mg/L. Fish exposed to different fenthion concentrations showed clinical signs such as erratic swimming, attempt to jump out of water, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 30 publications
2
0
0
Order By: Relevance
“…Therefore, this present study was designed to gain a clear understanding of the impact of cypermethrin on this particular sh species. It's important to note that behavioral changes in sh are among the most sensitive indicators of potential toxic effects resulting from pesticide exposure (Somdare et al 2015). Consistent with numerous previous investigations, pyrethroids have been shown to be toxic to freshwater shes, as evidenced by earlier studies.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, this present study was designed to gain a clear understanding of the impact of cypermethrin on this particular sh species. It's important to note that behavioral changes in sh are among the most sensitive indicators of potential toxic effects resulting from pesticide exposure (Somdare et al 2015). Consistent with numerous previous investigations, pyrethroids have been shown to be toxic to freshwater shes, as evidenced by earlier studies.…”
Section: Discussionsupporting
confidence: 78%
“…[54] Previously reported LC 50 values of glyphosate in C. gariepinus, T. zillii, O. niloticus, C. punctatus, Arabian pupfish (Aphanius dispar), Sheepshead minnow (Cyprinodon variegatus), and P. caudimaculatus were 0.05-43.65, [16] 211.80, [18] 16,8, [55] 32.540, [56] 115.25, [57] 240, [58] and 975 ppm, [59] respectively. The present study also showed that the glyphosate is nontoxic to C. gariepinus, in comparison to other pesticides, such as LC 50 of cypermethrin at 0.063 ppm, [60] diethyl phthalate at 3.931 ppm, [44] diazinon at 7.3 ppm, [61] fenthion at 39.97 ppm, [62] chlorpyrifos at 160 ppb, [63] acetamiprid at 265.7 ppm, lambdacyhalothrin at 0.00083 ppm and Acer at 0.210 ppm. [35] The 96 h-LC 50 of Atraforce was calculated and found to be 3.165 ppm.…”
Section: Mortalities Of C Gariepinus Juveniles Exposed To Acute Conce...supporting
confidence: 67%